Synthetical effect of microplastics and chiral drug amphetamine on a primary food source algae Chlorella pyrenoids. (November 2022) - Qu, Han; Wang, Fang; Barrett, Holly; Wang, Bin; Han, Jiajun; Wu, Junxue; Huang, Xiaochen; Hu, Yongxia; Yu, Gang
Abstract: The biological effects and fate of the chiral illicit drug amphetamine in the presence and absence of microplastics on freshwater algae ( Chlorella pyrenoids ), including acute toxicity, growth inhibition, photosynthetic pigment content, oxidative stress, lipid peroxidation, and enantioselective fate were assessed. An agglomeration and the shading effects of microplastics in algae suspension were also determined. Microplastics were observed to increase the toxicity of amphetamine to algae and reduce algae cell growth. Exposed Chlorella pyrenoids exhibited a reduced algae cell counts in an agglomeration test, wherein algae cells decreased between 18% and 56% among treatment groups exposed to 5–50 mg L −1 of microplastics. The agglomeration test suggested that microplastics might significantly increase the adverse effect on algae. Furthermore, our experiments demonstrated enantioselective degradation of amphetamine in algae, and demonstrated that the S-enantiomer was preferably degraded by algae cells. Adding microplastics to the algae suspension significantly reduced the enantioselectivity, with an EF value of 0.41 compared with amphetamine-alone group (0.34) after 21 d exposure. These results demonstrated the first evidence of microplastics acting as a vehicle to enhance amphetamine toxicity to Chlorella pyrenoids, as well as provided new insights into the co-effect of microplastics and organic contaminants on food source. Graphical abstract: Image 1 Highlights: Co-exposed with microplastics, the toxicity of amphetamine to algae cell was significantly increased. Microplastic could affect the photosynthesis and oxidative stress of algae cell. S-amphetamine was preferably degraded by algae cell. Microplastics could affect the enantioselective behavior of amphetamine.